2020
DOI: 10.1007/s00277-020-04082-7
|View full text |Cite
|
Sign up to set email alerts
|

Monosomal karyotype and chromosome 17p loss or TP53 mutations in decitabine-treated patients with acute myeloid leukemia

Abstract: TP53 aberrations reportedly predict favorable responses to decitabine (DAC) in acute myeloid leukemia (AML). We evaluated clinical features and outcomes associated with chromosome 17p loss or TP53 gene mutations in older, unfit DAC-treated AML patients in a phase II trial. Of 178 patients, 25 had loss of 17p in metaphase cytogenetics; 24 of these had a complex (CK+) and 21 a monosomal karyotype (MK+). In analyses in all patients and restricted to CK+ and MK+ patients, 17p loss tended to associate with higher r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 35 publications
4
11
0
Order By: Relevance
“…We did not find any association between TP53 alterations (including mutation and/or deletion) and response to azacitidine but an association with shorter OS which was significant in univariable analysis (12.6 months in TP53wt versus 7.9 months in TP53mut [p<0.001]] and just below the threshold of significance in multivariable analysis (HR = 1.49; 95% CI = [0.95-2.34]; p = 0.081). This finding is comparable to recent data from phase II trial testing frontline decitabine in AML deemed unfit for IC [7,41]. Survival outcomes in our cohort are also in line with the biomarker cohort of the phase 3 trial AZA-AML-001 [22], which have a median OS of 7.2 months in TP53mut patients compared to 12 months in TP53wt patients.…”
Section: Discussionsupporting
confidence: 89%
“…We did not find any association between TP53 alterations (including mutation and/or deletion) and response to azacitidine but an association with shorter OS which was significant in univariable analysis (12.6 months in TP53wt versus 7.9 months in TP53mut [p<0.001]] and just below the threshold of significance in multivariable analysis (HR = 1.49; 95% CI = [0.95-2.34]; p = 0.081). This finding is comparable to recent data from phase II trial testing frontline decitabine in AML deemed unfit for IC [7,41]. Survival outcomes in our cohort are also in line with the biomarker cohort of the phase 3 trial AZA-AML-001 [22], which have a median OS of 7.2 months in TP53mut patients compared to 12 months in TP53wt patients.…”
Section: Discussionsupporting
confidence: 89%
“…On the other hand, the multivariate analysis showed that only TP53 mutation and platelets not doubling after treatment were independent prognostic factors affecting the OS of patients. Although it has been reported that demethylating drugs such as decitabine could improve the remission rate of patients with TP53 mutation, they could not improve their OS [19,20], which is in line with our findings herein concerning survival of patients harboring TP53 mutation. Platelet doubling after treatment was a predictive indicator for patients to achieve remission.…”
Section: Discussionsupporting
confidence: 92%
“…Eight of 45 patients had TP53 mutations, and five of these patients also had 17p loss. CR, PR, and ALE rates were similar in patients with TP53 mutations and those with wild-type TP53, but OS appeared to be worse in patients with mutated TP53 (p = 0.036) [38].…”
Section: Tp53 Mutationsmentioning
confidence: 90%
“…TP53 aberrations seem to predict favorable responses to hypomethylating treatment with decitabine. Becker et al analyzed outcomes associated with chromosome 17p loss or TP53 gene mutations in unfit elderly patients with AML [38]. In that study, 25 of 178 patients had loss of 17p, of whom 24 had a complex (CK?)…”
Section: Tp53 Mutationsmentioning
confidence: 99%